2023
DOI: 10.1101/2023.01.30.526266
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IL-15 synergizes with CD40 agonist antibodies to induce durable immunity against bladder cancer

Abstract: CD40 is a central co-stimulatory receptor implicated in the development of productive anti-tumor immune responses across multiple cancers, including bladder cancer. Despite strong preclinical rationale, systemic administration of therapeutic agonistic antibodies targeting the CD40 pathway have demonstrated dose limiting toxicities with minimal clinical activity to date, emphasizing an important need for optimized CD40-targeted approaches, including rational combination therapy strategies. Here, we describe an … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…In both the MB49 and UPPL1541 models, anti-CD40 agonist antibodies caused upregulation of IL-15Rα on dendritic cells (DCs) and other myeloid populations. Moreover, using CD40- and FcγR-humanized C57BL/6J mice harbouring MB49 or UPPL1541 tumours, it was shown that the human anti-CD40 agonist antibody 2141-V11 caused reduced tumour size and that this effect was enhanced by cotreatment with IL-15 [37 ▪ ].…”
Section: In Vivo Modelsmentioning
confidence: 99%
“…In both the MB49 and UPPL1541 models, anti-CD40 agonist antibodies caused upregulation of IL-15Rα on dendritic cells (DCs) and other myeloid populations. Moreover, using CD40- and FcγR-humanized C57BL/6J mice harbouring MB49 or UPPL1541 tumours, it was shown that the human anti-CD40 agonist antibody 2141-V11 caused reduced tumour size and that this effect was enhanced by cotreatment with IL-15 [37 ▪ ].…”
Section: In Vivo Modelsmentioning
confidence: 99%